Connecting the Present to the Past: Furthering the Research on Bilingual Education and Bilingualism. (March 2016) - Baker, Doris Luft; Basaraba, Deni Lee; Polanco, Paul
The authors of this chapter review empirical studies that have been conducted in bilingual education to propose a future research agenda that incorporates the most recent evidence on the effectiveness of bilingual programs, advances in neuroscience, and the body of evidence of the benefits of being bilingual and biliterate. They first describe the historical and sociopolitical precedent of how bilingual education came to play a determinant role in U.S. education. Next, they summarize reviews that have been conducted examining the effects of bilingual education on the academic performance of English learners from 1985 until 2003. They then review the research on bilingual education since 2003. Although the majority of studies reviewed focused on reading, the authors also found studies that compared the effects of bilingual programs on other academic outcomes such as writing, science, and mathematics, inside and outside the United States. In addition, they address the benefits of bilingualism on cognition and discuss the research on cross-linguistic transfer to help the reader better understand the transfer of skills between the native language and the second language within the context of bilingual programs. They end the chapter with recommendations for future research.